The Relevance of Gender Equality from Asghar Ali Engineer's Feminist Perspective on the SDGs - Sari, Melani Novita (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
Gender equality is one of the goals to achieve a sustainable and better life in facing global challenges. This research is a literature study using descriptive-analytical method. The approach used is a philosophical-critical approach. The philosophical-critical approach is necessary because it aims to pursue the researcher's ideas that can have an impact on substantial matters in society. This exploration tries to reveal the harmonization of Asghar Ali Engineer's feminist perspective of gender equality with Islam and its relevance to the SDGs critically. Data sources in this research are obtained by collecting primary and secondary data. The results of this study show that in Asghar Ali Engineer's view, men and women both have rights in the social sphere that refer to the principles of justice and humanity. Engineer refers to the Qur'an to show that the holy book explicitly recognizes that people must be treated fairly, regardless of gender, and must accept the consequences of their actions in the same way, whether they are men or women. The inherited patriarchal culture is due to differences in understanding. Engineer's view shows that religion can be a solution when understood normatively and contextually, including to realize the SDGs.